PENGEMBANGAN MODEL PERMAINAN BOLA BASKET TAKI SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN JASMANI,OLAHRAGA DAN KESEHATAN SISWA SEKOLAH DASAR KELAS ATAS DI KOTA GORONTALO - Pauweni, Mirdayani (Jurnal Health and Sport, 2011)
the result of this research was a product of basket ball model as teaching media of physical education, sport and health. Based on the large scale experimenq it found if total score fiequency of psychomotor aspect,cognitive aspect, affective aspect, shows that th ere 94,50% of218 score total students involved in good category,5,50% of 218 seore total students involved in average category, and no one score total students involved in lack category. The total score describing ofbasic competence attainment in instructional process ofphysical, sport, and health edrcation through using taki basket.